2021
DOI: 10.12776/qip.v25i2.1594
|View full text |Cite
|
Sign up to set email alerts
|

Effective TQM Implementation in the Service Industry: A Proposed Framework

Abstract: Purpose: This paper aims to explore the framework, practices, and implementation of total quality management (TQM) in the service industry. Methodology/Approach: The present study focuses on the existing literature on several TQM dimensions and developed a framework that would allow the service industry to efficiently apply TQM, resulting in enhanced organizational performance. Findings: The research findings suggest that the relevance and implementation of TQM practices have a strong linkage to organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…In a recent study conducted on the healthcare industry, Ansari (2022) documented that committed leadership and supportive infrastructure are the primary driving forces to improve service quality resulting in customer satisfaction and loyalty. Some researchers also empirically demonstrated that TQM in the service industry is essential for enhancing organizational performance (Magd et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study conducted on the healthcare industry, Ansari (2022) documented that committed leadership and supportive infrastructure are the primary driving forces to improve service quality resulting in customer satisfaction and loyalty. Some researchers also empirically demonstrated that TQM in the service industry is essential for enhancing organizational performance (Magd et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kandemir and Jamieson (2002) found that training programmes in the South African financial sector have contributed to performance improvement by enhancing employee knowledge, skills, abilities, competencies, and behaviours within the banking industry (Mehale 2021;Lethepa et al 2020). This aligns with the principles of TQM, which emphasise the involvement of all members of an organisation in improving procedures, products, services, and the workplace (Karami et al 2021;Magd et al 2021;Ali 2021).…”
Section: History Of Total Quality Management Implementation In the So...mentioning
confidence: 58%
“…There was a need to find answers to these questions, which could positively affect organizational performance due to enhanced total quality management. According to Magd et al (2021), total quality management practices will have a strong linkage to organizational performance. It can further promote the organization in adoption and willingness to invest in BCT for supply chain optimization.…”
Section: Research Questionsmentioning
confidence: 99%